The Role of Country Concentration in the International Portfolio Investment Positions for the European Union Members - Brushko, Iuliia (IMF Working Papers; Working Paper, 2014)
This paper examines the international portfolio flows of European Union. Our analysis includes three dimensions: (1) the level of countries portfolio investment concentration (those who invest evenly among counterparties versus those who invest more heavily in some counterparties); (2) the share of total portfolio investment assets invested at the destination; and (3) pre- and during the crisis periods. We find that portfolio investment positions respond differently to macroeconomic variables depending on the level of investment concentration and the share of invested assets. In particular, variables of health of the financial system become important determinants for portfolio investment during the crisis.